Influencia del habla y del lenguaje en el desarrollo del aprendizaje, de los estudiantes de tercer año de educación básica de la Escuela 5 de Junio, Parroquia Isla de Bejucal del Cantón Baba Provincia de Los Ríos - Muñoz Schuldt, Paola Emperatriz (2020)
In most of the schools from initial to seventh grade of basic education we find teachers worried and upset at the same time, due to the lack of collaboration of parents in homework, clothing, student health without neglecting those that present difficulties in their learning; Within which the most common are related to their involvement in language and the form of speech within the most common we can find dyslexia, dyspraxia, dysortography among others. The intention of this project is to recognize students with speech and language problems that affect their learning, In addition to knowing the possible causes of this problem from home, knowing the parents and teaching them basic rules so that they can detect in a minor child own or family to recognize at an early age this difficulty on the other hand also the teacher can use this document as a tool that identifies children with difficulty and proposes strategies that although they seem simple will be of great importance for their application and will help the student to modify his lack of strength to improve his personality and self-esteem, therefore improve his language and overcome his speech problems.